Interactivity factors and student engagement in the use of emerging technologies in higher education / Norazah Abdul Aziz ... [et al.] - Abdul Aziz, Norazah; Chan, Yuen Fook; Sidhu, Gurnam Kaur; Narasuman, Suthagar; Zulkifli, Ahmad Fahim (Universiti Teknologi MARA, 2024)
The global COVID-19 pandemic witnessed unprecedented challenges in all aspects of our lives, including higher education. One of the key challenges is that lessons are delivered almost on the fly, with both lecturers and students adjusting to the flow of the lessons. A popular solution adopted in teaching and learning at all levels is integrating various emerging technologies, including Google Classroom and Team Meeting, live streaming, and cloud platforms. Using the six learning types (acquisition, inquiry, discussion, practice, collaboration, and production) based on Laurillard's (2012) Conversational Framework, this quantitative study examined to what extent emerging technologies and interactivity factors have impacted student learning engagement in the context of online classrooms. Hence, this quantitative study entails a survey questionnaire to obtain insights into the phenomena of emerging technologies as teaching and learning tools and their impact on student learning engagement from students' perspectives. 103 undergraduate students were selected randomly at the Faculty of Education from a public university in Selangor. The study used descriptive and inferential statistical analysis to answer the research questions. The study's outcome demonstrated that student learning engagement was not affected by gender, the discipline of research or CGPA. Student and content factors were more associated with student learning engagement than instructor factors. Multiple regression analysis indicated that student and content factors contributed significantly to student learning engagement. However, instructor factors, emerging technologies and online platforms did not impact student learning engagement in the online classroom. This study implies that higher learning institutions should pay more attention to student and content factors while designing online lessons. Emerging technologies, online platforms and instructor factors are supposed to support online learning, but they are not the determining factors for the success of online learning.